2012
DOI: 10.3182/20120711-3-be-2027.00417
|View full text |Cite
|
Sign up to set email alerts
|

Non-Asymptotic Confidence Regions for the Least-Squares Estimate

Abstract: We propose a new finite sample system identification method, called Sign-Perturbed Sums (SPS), to estimate the parameters of dynamical systems under mild statistical assumptions. The proposed method constructs non-asymptotic confidence regions that include the leastsquares (LS) estimate and are guaranteed to contain the true parameters with a user-chosen exact probability. Our method builds on ideas imported from the "Leave-out Sign-dominant Correlation Regions" (LSCR) approach, but, unlike LSCR, also guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 5 publications
0
44
0
Order By: Relevance
“…In Campi and Weyer [2005], Dalai et al [2007], Csáji et al [2012], two new approaches named LSCR and SPS are described for the exact characterization of parameter uncertainty in non-asymptotic conditions. Their most striking feature is that they avoid a large number of the usual assumptions about the noise corrupting the data.…”
Section: Characterizing Parameter Uncertainty With the Lscr Approachmentioning
confidence: 99%
“…In Campi and Weyer [2005], Dalai et al [2007], Csáji et al [2012], two new approaches named LSCR and SPS are described for the exact characterization of parameter uncertainty in non-asymptotic conditions. Their most striking feature is that they avoid a large number of the usual assumptions about the noise corrupting the data.…”
Section: Characterizing Parameter Uncertainty With the Lscr Approachmentioning
confidence: 99%
“…This limitation makes the new methods LSCR and SPS proposed by Campi and coworkers particularly interesting [1], [3], [4].…”
Section: Spsmentioning
confidence: 99%
“…In [3], it has been shown that p * belongs to Σ q with exact probability 1 − q/m. Σ q may be defined more formally as…”
Section: Spsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a vector p of parameters of some approximate mathematical model is estimated from a noisy data vector y, this is usually via the minimization of some cost function J (p), for instance J (p) = y − y m (p) 2 2 , where y m (p) is the vector of model outputs, assumed here to be a deterministic function of p and · 2 is a (possibly weighted) ℓ 2 norm. Then…”
Section: Introductionmentioning
confidence: 99%